Une leçon clinique à la Salpetriere, 1887: trois conceptions de la mise en scene theatrale (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Our premise is that the method of teaching at the bedside at the Salpêtrière hospital – about hysteric disease – at the end of the nineteenth century and all the various conceptions of staging and direction in theatre at the same period partake of the same cultural juncture, characterized by a circulation ‒ transfers through contact, shifts and superpositions ‒ of different experiences in the act of looking. This paper examines three of such experiences, which were particularly common in theatres in Paris at the turn of the twentieth century: the clinical experience of looking, developed by André Antoine at the Théâtre-Libre; the haptic experience found in spectacular shows, with the Grand Guignol as one of its prime examples, and the hypnotic experience in the staging of symbolist theatre.